Recognition and understanding of construction safety signs by final year engineering students - Frank Kulor; Elisha D. Markus; Michael W. Apprey; Divine Novieto (Universitas Ahmad Dahlan, 2025)
This study assessed the recognition and understanding of construction safety signs among final-year Higher National Diploma, Building Technology (BT) and Electrical/Electronic Engineering (EE) students at a technical university in Ghana. The purpose was to evaluate their awareness of safety signs, addressing gaps in existing research and providing updated data to enhance occupational safety training. A descriptive statistical methodology was employed, utilizing purposive sampling to survey 137 students via structured questionnaires. Data were analyzed using SPSS v16 and compared against ISO 3864 and ANSI Z5353 standards. Results revealed varying comprehension rates: prohibition signs (61.71%), general warning signs (71.08%), mandatory signs (78.32%), emergency escape signs (81.4%), firefighting signs (86.9%), and chemical labeling signs (77.98%). While mean scores exceeded benchmark thresholds, low response rates for specific signs indicated significant knowledge gaps. The study concludes that unfamiliarity with safety signs persists due to insufficient training and curricular emphasis. Recommendations include revising academic syllabi under Ghana Tertiary Education Commission and National Board for Technical Examinations guidelines to integrate safety education, alongside industry partnerships for practical training during internships. These measures aim to reduce workplace accidents and improve safety compliance among future engineers.